1998
DOI: 10.1046/j.1365-2435.1998.00231.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of floral morphology and display on outcrossing in Blue Columbine, Aquilegia caerulea (Ranunculaceae)

Abstract: The hermaphrodite sexual system possessed by most flowering plants creates the potential for close inbreeding through self-pollination. While many species strongly limit self-fertilization with self-incompatibility, about one-third of hermaphrodite taxa are selfcompatible (Richards 1986) and the balance between outcrossing and self-fertilization will depend, in part, on the relative deposition of self-and cross-pollen on stigmas (Holsinger 1992). This, in turn, can be influenced by both intrinsic and extrinsic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
124
2

Year Published

1999
1999
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(131 citation statements)
references
References 69 publications
5
124
2
Order By: Relevance
“…The results support the role of anther-stigma separation in decreasing individual selfing rate, as reported in other diverse taxa such as Lycopersicon pimpinellifolium (Rick et al, 1978), Datura stramonium (Motten and Stone, 2000), and Aquilegia caerulea (Brunet and Eckert, 1998).…”
Section: Effects Of Herkogamy On Outcrossing Ratesupporting
confidence: 88%
See 2 more Smart Citations
“…The results support the role of anther-stigma separation in decreasing individual selfing rate, as reported in other diverse taxa such as Lycopersicon pimpinellifolium (Rick et al, 1978), Datura stramonium (Motten and Stone, 2000), and Aquilegia caerulea (Brunet and Eckert, 1998).…”
Section: Effects Of Herkogamy On Outcrossing Ratesupporting
confidence: 88%
“…Recently, researchers have begun to investigate the effects of floral variation on individual outcrossing rates within a population (Barrett et al, 1994;Brunet and Eckert, 1998;Vrieling et al, 1999;Motten and Stone, 2000). Current procedures for estimating population-level outcrossing rates are quite robust if multiple loci are included in the study (Ritland and Jain, 1981).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of a significant difference in the mean outcrossing rates of the two herkogamy classes is surprising for two reasons. First, most other studies that considered herkogamy variation among individuals found significantly diminished outcrossing in low-herkogamous individuals (e.g., Karron et al 1997;Brunet and Eckert 1998;Takebayashi et al 2006;Herlihy and Eckert 2007). Second, the absolute amount of herkogamy difference between classes was shown to greatly affect seed set under pollinator exclusion , demonstrating that the autonomous component of selfing is affected by herkogamy.…”
Section: Effects Of Herkogamy On Matingmentioning
confidence: 94%
“…In self-compatible species, herkogamy has been mainly proposed as a mechanism to limit selfing, but it also influences sexual interference between male and female floral functions (Barrett 2002). Herkogamy negatively affects seed set when pollinators are absent (e.g., Luijten et al 1999;Moeller 2006;de Vos et al 2012), and several genetic analyses confirmed the expected positive correlation between herkogamy and outcrossing rates, both among (e.g., Rick et al 1977;Holtsford and Ellstrand 1992;Luo and Widmer 2013) and within populations (e.g., Karron et al 1997;Brunet and Eckert 1998;Takebayashi et al 2006;Herlihy and Eckert 2007;Weber et al 2012; but see Medrano et al 2005Medrano et al , 2012. Importantly, herkogamy is known to decrease during anthesis in some species, potentially increasing opportunity for autonomous selfing in later stages of anthesis (Luijten et al 1999;Armbruster et al 2002;Duan et al 2010;de Vos et al 2012).…”
Section: Introductionmentioning
confidence: 97%